1973
DOI: 10.1073/pnas.70.5.1298
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Directed DNA Polymerase and Virus-Induced Leukemia in Mice

Abstract: Rifamycin antibiotics, which inhibit RNAdirected DNA polymerase of Rauscher leuckemia virus, prevent the leukemogenic activity of the virus, and the effect of leukemogenesis correlates with the magnitude of inhibition of the purified enzyme. This inhibition of enzyme activity by rifamycin SV derivatives is due to a relatively tight binding between the enzymes and the inhibitors, yet the binding can be reversed by nonionic detergent. The results of this study suggest that RNAdirected DNA polymerase is essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The totality of these studies have suggested that SvCx inhibits an event(s) directly associated with the action of oncogenic viruses rather than with the proliferation of neoplastic cells (5). An inhibition might result from the direct interaction of streptovaricin with the virion, resulting in blockage of the virion-associated reverse transcriptase present in leukemogenic viruses, as has been postulated by Wu et al with other ansamycin compounds (16).…”
mentioning
confidence: 99%
“…The totality of these studies have suggested that SvCx inhibits an event(s) directly associated with the action of oncogenic viruses rather than with the proliferation of neoplastic cells (5). An inhibition might result from the direct interaction of streptovaricin with the virion, resulting in blockage of the virion-associated reverse transcriptase present in leukemogenic viruses, as has been postulated by Wu et al with other ansamycin compounds (16).…”
mentioning
confidence: 99%
“…More recently, SvCx has shown potent, and surprisingly selective, activity against functions of oncornaviruses both in cell culture (6) and mice (2). The mechanism of action of SvCx is not firmly understood, but it may be related to the known ability of SvCx to block the ribonucleic acid-dependent deoxyribonucleic acid polymerase present in ribonucleic acid tumor viruses (3,5,12,14); it is clear that blockade of bacterial and bacteriophage function is mediated at the level of polymerase function (4).…”
mentioning
confidence: 99%
“…Specific antiviral effects of ansamycins have been demonstrated on several different levels of biological organization, such as inhibition ofreverse transcriptase (6,10,11,19), activity apparently directed against the virus particle itself (13,14,28), inhibition of murine and avian sarcoma virus production and transformation in cell culture (3,8,16,20,27), reduction of splenomegaly in Rauscher disease in vivo (4,5), and cytotoxic activity against human leukemic blasts (22). The mechanism of action of these drugs on RNA tumor virus functions is not firmly understood, but in several instances it has been correlated apparently with an ability to inhibit the RNA-dependent deoxyribonucleic acid polymerase (6,10,11,18,19,28). It has, however, never been determined whether the replicationdefective transforming particles or the accompanying helper viruses are the primary drug targets.…”
mentioning
confidence: 99%
“…Two compounds are derivatives of rifamycin SV, well characterized as to their potent inhibition of reverse transcriptase and activity against Rauscher virus-induced splenomegaly (25,28): compound no. 120, 2,6-dimethyl benzyl 4-demethyl rifampin ( (Fig.…”
mentioning
confidence: 99%